Trait response of three Baltic Sea spring dinoflagellates to temperature, salinity, and light gradients - Haraguchi, Lumi; Kraft, Kaisa; Ylöstalo, Pasi; Kielosto, Sami; Hällfors, Heidi; Tamminen, Timo; Seppälä, Jukka (Frontiers in Marine Science, 2023)
Climate change is driving Baltic Sea shifts, with predictions for decrease in salinity and increase in temperature and light limitation. Understanding the responses of the spring phytoplankton community to these shifts is essential to assess potential changes in the Baltic Sea biogeochemical cycles and functioning. In this study we use a high-throughput well-plate setup to experimentally define growth and the light acquisition traits over gradients of salinity, temperature and irradiance for three dinoflagellates commonly occurring during spring in the Baltic Sea, Apocalathium malmogiense, Gymnodinium corollarium and Heterocapsa arctica subsp. frigida. By analysing the response of cell volume, growth, and light-acquisition traits to temperature and salinity gradients, we showed that each of the three dinoflagellates have their own niches and preferences and are affected differently by small changes in salinity and temperature. A. malmogiense has a more generalist strategy, its growth being less affected by temperature, salinity, and light gradients in comparison to the other tested dinoflagellates, with G. corollarium growth being more sensitive to higher light intensities. On the other hand, G. corollarium light acquisition traits seem to be less sensitive to changes in temperature and salinity than those of A. malmogiense and H. arctica subsp. frigida. We contextualized our experimental findings using data collected on ships-of-opportunity between 1993-2011 over natural temperature and salinity gradients in the Baltic Sea. The Apocalathium complex and H. arctica subsp. frigida were mostly found in temperatures<10°C and salinities 4-10 ‰, matching the temperature and salinity gradients used in our experiments. Our results illustrate that trait information can complement phytoplankton monitoring observations, providing powerful tools to answer questions related to species’ capacity to adapt and compete under a changing environment.